2002
DOI: 10.1155/2002/623213
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Radiological Imaging in the Diagnosis of Acute Appendicitis

Abstract: Several strategies have been employed to improve the accuracy of the diagnosis of appendicitis and to reduce the associated perforation rate. Because clinical algorithms have been disappointing, many physicians resort to radiological modalities. Plain abdominal x-rays are nonspecific, barium enema examination has relatively low accuracy, scintigraphy scans require considerable time and are difficult to interpret, and magnetic resonance imaging is relatively unstudied. The most promising modalities are graded c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 181 publications
0
14
0
1
Order By: Relevance
“…Early diagnosis is crucial to the success of therapy [1,2,21]. Currently, CT is being used for differential diagnosis of acute abdomen such as appendicitis, especially in patients with undetermined and inconclusive ultrasound findings.…”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosis is crucial to the success of therapy [1,2,21]. Currently, CT is being used for differential diagnosis of acute abdomen such as appendicitis, especially in patients with undetermined and inconclusive ultrasound findings.…”
Section: Discussionmentioning
confidence: 99%
“…Acute appendicitis is the most common surgical emergency in childhood, constituting 1%-2% of all children admitted to the paediatric emergency ward [1,2,3]. Those with the typical symptoms and signs of acute appendicitis or suspected cases with definite findings of peritonitis are promptly indicated for surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Once the appendix ruptures, which is very common in preschool-age children with appendicitis, the ultrasound findings disappear and are replaced by peritoneal fluid and thickened bowel loops, and the diagnostic accuracy is reduced. Although many reports of appendicitis among school-age children have been published, few investigators have focused on the diagnostic difficulties of diagnosing appendicitis in preschool age children [1,6,7,8,9,10,11]. We analysed retrospectively our experience of emergency appendectomies in patients below 5 years of age over an 11-year period.…”
Section: Introductionmentioning
confidence: 99%
“…1 The diagnosis of acute appendicitis relies largely on clinical assessment, although both ultrasound and computed tomography (CT) can be helpful. 2,3 Over the years, many studies have looked at various simple blood tests and clinical criteria in an attempt to improve diagnostic accuracy. The white cell count (WCC) and C-reactive protein (CRP) are now often used to guide clinical assessment but past studies have demonstrated sensitivities of CRP measurements ranging from 40% to 94%, and specificities of 38-87%.…”
mentioning
confidence: 99%